2007
DOI: 10.1001/archsurg.142.10.923
|View full text |Cite
|
Sign up to set email alerts
|

Death Rates and Causes of Death After Bariatric Surgery for Pennsylvania Residents, 1995 to 2004

Abstract: Background: Bariatric surgery has emerged as the most effective treatment for class III obesity (body mass index, Ն40). The number of operations continues to increase. We measured case fatality and death rates by time since operation, sex, age, specific causes of death, and mortality rates. Design and Setting: Data on all bariatric operations performed on Pennsylvania residents between January 1, 1995, and December 31, 2004, were obtained from the Pennsylvania Health Care Cost and Containment Council. Matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
3
15

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 36 publications
6
81
3
15
Order By: Relevance
“…Unfortunately, causes of death were not consistently reported in included studies; only Overby et al [12] reported one out of three deaths related to PE. It has been reported that some unexplained deaths after bariatric surgery may be related to undiagnosed PE [1,12,14,16] , so this can be a cause of death that should be explored.…”
Section: Mortality Related To Prophylactic Ivc Filter Placement Beformentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, causes of death were not consistently reported in included studies; only Overby et al [12] reported one out of three deaths related to PE. It has been reported that some unexplained deaths after bariatric surgery may be related to undiagnosed PE [1,12,14,16] , so this can be a cause of death that should be explored.…”
Section: Mortality Related To Prophylactic Ivc Filter Placement Beformentioning
confidence: 99%
“…However, pulmonary embolism (PE) remains the second leading cause of perioperative mortality after anastomotic leak, accounting for almost 40% of perioperative deaths after bariatric surgery [1] . Lack of randomized controlled trials to guide thromboprophylaxis after bariatric surgery makes clinical decision making difficult among patients considered as high risk for VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Após o bypass gástrico, os pacientes desenvolvem maior vulnerabilidade aos seus efeitos (rápida absorção e níveis séricos mais elevados) 86 , o que teoricamente os torna mais suscetíveis tanto às propriedades sistêmicas lesivas quanto aos efeitos psicotrópicos associados com acidentes por imprudência/impulsividade, sintomas depressivos e suicídio. Como visto anteriormente, de fato há maior incidência de mortes por abuso de substâncias (especialmente álcool) e acidentes automobilísticos nas grandes casuísticas com seguimento de pacientes bariátricos 3,4,24,87,88 .…”
Section: Seguimento Pós-operatóriounclassified
“…Além disso, houve mais 14 óbitos relacionados com alcoolismo, bulimia e acidentes de trânsito, condições comumente associadas com comportamento impulsivo. De modo semelhante, Omalu et al 4 observaram aumento substancial no número de suicídios entre 16.683 pacientes bariátricos comparados à média da população em um perío-do de 10 anos. Além disso, os autores avaliam que a taxa de suicídio (16 casos) tenha sido subestimada porque os óbitos por overdose (14 casos) foram excluídos.…”
unclassified
See 1 more Smart Citation